Reliability of a New Swept-Source Optical Coherence Tomography Biometer in Healthy Children, Adults, and Cataract Patients - Jinhai Huang; Yuyu Zhao; Giacomo Savini; Guanshun Yu; Jinjin Yu; Zhongxing Chen; Ruixue Tu; Yune Zhao (Journal of Ophthalmology)
Purpose. To comprehensively assess the reliability of a new optical biometer (IOLMaster 700), based on swept-source optical coherence tomography (SS-OCT) and comparison with a standard biometer (IOLMaster 500), in healthy children, adults, and cataract patients. Methods. A total of 301 eyes from 301 consecutive subjects were enrolled prospectively. Two experienced operators measured each eye three times consecutively with the IOLMaster 700. The axial length (AL), keratometry (K), anterior chamber depth (ACD), lens thickness (LT), central corneal thickness (CCT), and white-to-white (WTW) distance were recorded. Intraoperator repeatability and interoperator reproducibility of the IOLMaster 700 were analyzed using the test-retest (TRT), coefficients of variation (CoV), and intraclass correlation coefficients (ICCs). The agreement between the two devices was evaluated using the Bland–Altman method. Results. The repeatability and reproducibility of the SS-OCT optical biometer were high for all ocular biometry parameters in all groups, except for the WTW in cataract patients (TRT, 0.27–0.44 mm; ICC, 0.86–0.95). The reproducibility of averaged measurements from three consecutive readings (TRT : AL = 0.02 mm, CCT = 5.41 μm, ACD = 0.03 mm, LT = 0.03 mm, Km = 0.17 D, and WTW = 0.22 mm) was higher than the reproducibility of single measurements (TRT : AL = 0.04 mm, CCT = 7.43 μm, ACD = 0.06 mm, LT = 0.05 mm, Km = 0.26 D, and WTW = 0.35 mm) in the three groups. The consistency in the data between the two biometers was high, with narrow 95% LoAs in the three groups. Conclusion. Repeatability and reproducibility of the new SS-OCT optical biometer were excellent and consistent with that of the standard biometer with respect to healthy children, healthy adults, and cataract patients.